Lithuania : The Transition to a Market Economy - World Bank (The World Bank, 1993)
Lithuania has embarked on a comprehensive and far-reaching economic reform program aimed at reorienting its economy from a centrally planned to a market system. Substantial progress has already been made in the transition to a market economy. In some areas - such as privatization - Lithuania has made the transition more quickly than most other countries in a comparable position. However, the reforms have started in an unfavorable economic environment, indicated by declining output, deteriorating terms of trade, and high rates of inflation. This study presents the first comprehensive assessment of the Lithuanian economy prepared by the World Bank. It is composed of three parts. Part I provides an overview of recent developments and presents a reform agenda for the medium term; Part II examines in detail macroeconomic and systemic reform issues; and Part III contains discussions of individual sectors. Quantitative information is presented in a statistical appendix